2015
DOI: 10.1007/s00167-015-3752-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of high tibial osteotomy in the treatment of knee laxity: a comprehensive review

Abstract: Knees with chronic instability pose a difficult treatment challenge. In all cases, the contribution of coronal plane alignment to varus-valgus knee stability must be carefully considered and addressed prior to ligament surgery. Sagittal plane alignment is also key and must not be overlooked. Such considerations drive the indication for osteotomy as well as the type of osteotomy that is chosen. Level of evidence IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 36 publications
1
47
0
2
Order By: Relevance
“…As a mature method of “knee preservation,” HTO has been widely used in the treatment of unicompartmental knee osteoarthritis. The operation principle of HTO is to transfer the pressure load in unicompartment by adjusting the force line of the lower extremities so as to relieve pain, restore knee joint function, and prolong knee joint life [ 5 ]. Numerous studies have shown that HTO has been proven to be a reliable treatment with good short- and medium-term efficacy for KOA after years of clinical practice [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a mature method of “knee preservation,” HTO has been widely used in the treatment of unicompartmental knee osteoarthritis. The operation principle of HTO is to transfer the pressure load in unicompartment by adjusting the force line of the lower extremities so as to relieve pain, restore knee joint function, and prolong knee joint life [ 5 ]. Numerous studies have shown that HTO has been proven to be a reliable treatment with good short- and medium-term efficacy for KOA after years of clinical practice [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the treatment of unicompartmental OA, osteotomies around the knee are increasingly performed as a concomitant treatment to correct alignment in ligament reconstruction, articular cartilage restoration procedures, and meniscal repair or transplantation surgery [2226]. In these patients, who are mostly younger and more active, the function of the osteotomy is to (1) reduce strain on the reconstructed ligament graft or the posterolateral corner in cases of varus alignment or (2) unload the involved compartments and thereby reduce stress to the biological repair tissue and potentially prevent or postpone progression of early knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…1 When treating ligamentous instability, PTO can be performed in isolation, with simultaneous ligament reconstruction or as a staged procedure with PTO first followed by ligament reconstruction in cases of persistent instability. A recent systematic review 19 reported favorable outcomes of combined PTO and ligamentous procedures. Studies with combined ACL reconstruction and PTO tended to report higher postoperative activity levels when compared with PTO alone.…”
Section: Discussionmentioning
confidence: 99%